1984
DOI: 10.3171/jns.1984.61.1.0076
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical brain injury: the sympathoadrenal response

Abstract: Catecholamine release was studied in cats as a function of injury severity in the fluid-percussion model of brain injury. Hyperglycemia was also studied as a function of catecholamine response and injury severity. Epinephrine (E) and norepinephrine (NE) increased as a function of injury. This increase was maximal at about a 3.0-atmosphere (atm) injury level and amounted to a 500-fold increase for E and 100-fold increase for NE. Both catecholamines increased maximally by 10 seconds postinjury. Glucose increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
1
3

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(89 citation statements)
references
References 41 publications
5
80
1
3
Order By: Relevance
“…A prevalência da hiperglicemia devido a trauma craniano é considerada alta na literatura publicada 3,6,7 . A fisiopatologia da hiperglicemia não é totalmente compreendida, apesar de várias hipóteses terem sido sugeridas.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A prevalência da hiperglicemia devido a trauma craniano é considerada alta na literatura publicada 3,6,7 . A fisiopatologia da hiperglicemia não é totalmente compreendida, apesar de várias hipóteses terem sido sugeridas.…”
Section: Discussionunclassified
“…A causa dessa condição é descrita como multifatorial e relacionada ao estresse pós-traumático. A resposta metabólica súbita ao trauma poderia incluir grandes alterações nos níveis de cortisol circulante, glucagon e epinefrina, resultando em alteração no metabolismo da glicose, associada com resistência à insulina, níveis elevados de glicose no sangue e nos tecidos, acidose intracelular, acúmulo de lactato, insuficiência energética, e, consequentemente, lesão neuronal 2,3 . Distinguir a relação causa e efeito entre hiperglicemia e má evolução após TC continua sendo uma tarefa difícil.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Increased permeability of the alveolocapillary membrane secondary to an elevation in catecholamines has been invoked [5]. It was shown that catecholamines dramatically increase after a variety of central nervous system insults [10]. And massive alphaadrenergic stimulation is thought to have an important role in the initial phase of neurogenic pulmonary edema [11].…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography of head was negative for subarachnoid hemorrhage, but angiography revealed a large aneu- tension has been described to be a result of the reflex increase of catecholamine secretion, [6][7][8] and a result of the sympathetic overactivity due to brainstem compression, 9 or due to craniocaudal ischemia. [10][11][12][13] Some animal studies suggest Cushing's response is a late feature, when ICP approaches mean arterial pressure, signalling breakdown of cerebral autoregulation. [14][15][16][17] In this situation, hypertension leads to further increase of ICP, adversely influencing cerebral perfusion.…”
Section: Case Reportmentioning
confidence: 99%